Virtual Reality versus Real–World Space: Comparing Perceptions of Brightness, Glare, Spaciousness, and Visual Acuity. Issue 2 (June 2022) - Jin, Xu; Meneely, Jason; Park, Nam–Kyu
Virtual reality (VR) headsets exhibit great potential for conducting interior design research in immersive digital settings; however, additional studies are needed to map out limitations for their use to simulate real–world settings. We investigated how participant perceptions of a single interior environment varied among a real–world space (R) and two surrogate VR spaces (one made with 360° spherical photography and one made with 360° spherical digital rendering). A total of 42 undergraduate, interior design students were randomly assigned to one of two experiments, resulting in two groups of 21 students. Each participant completed a visual acuity task and evaluated perceived brightness, glare, and spaciousness within the real–world space and one of the two surrogate VR environments. Participants reported acceptable baseline levels of perceived realism in both VR environments. There was no significant difference between the rendered–VR simulation and real–world space for brightness, glare, and spaciousness, while the photographed–VR simulation was seen as significantly brighter and glaring. Performance on the visual acuity task was significantly lower in both VR simulations than in the real–world–approximating the difference between 20/20 and 20/60 vision. Implications and strategies for effective deployment of VR simulations in interior design research are discussed.